1988
DOI: 10.1212/wnl.38.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome in Rochester, Minnesota, 1961 to 1980

Abstract: The incidence of carpal tunnel syndrome in the population of Rochester, Minnesota, from 1961 through 1980 was determined by use of the medical records-linkage system of the Rochester Epidemiology Program Project at the Mayo Clinic; 1,016 patients (1,600 affected hands) were identified. Incidence (cases per 100,000 person-years) was 99 (crude) overall, whereas the age-adjusted rates were 52 for the men, 149 for the women, and 105 for both sexes combined. Age-adjusted incidence rates increased from 88 during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
154
3
6

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(172 citation statements)
references
References 0 publications
9
154
3
6
Order By: Relevance
“…5,6 In a study conducted in England 7 , the incidence of CTS in women and men was found to be 0.19% and 0.088% respectively. In another study, 8 the incidence rate was reported as 0.099, with a female to male ratio of 3:1.…”
Section: Introductionmentioning
confidence: 93%
“…5,6 In a study conducted in England 7 , the incidence of CTS in women and men was found to be 0.19% and 0.088% respectively. In another study, 8 the incidence rate was reported as 0.099, with a female to male ratio of 3:1.…”
Section: Introductionmentioning
confidence: 93%
“…A male-to-female ratio of 1:3 was described in a population study (39). There is yet no evidence for an increased female susceptibility for work-related CTS when exposure is controlled for.…”
Section: Confounding and Individual Susceptibilitymentioning
confidence: 97%
“…A STC é mais comum entre mulheres, atingindo pico de prevalência entre 45-54 anos 10 . As taxas de prevalência variam de acordo com a metodologia utilizada.…”
Section: Epidemiologia Epidemiologia Epidemiologia Epidemiologia Epidunclassified
“…Certas manobras, como os testes de Tinel e Phalen, podem provocar os sintomas. Estes testes produzem alto número de resultados falso-positivos e falso-negativos, faltando pois especificidade e sensibilidade, o que os torna limitados como sinais clínicos 4,[10][11][12][13] .…”
unclassified